Implementasi Pembelajaran Pendidikan Agama Islam Berlandaskan Nilai-Nilai Karakter di Sekolah Dasar Laboratorium Universitas Negeri Malang - Rahmat Rahmat (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2018)
Islamic religious education is one of the compulsory subjects in public schools at all levels and ranks. As for in the madrassa, an Islamic religious education, better known as a group of Islamic religious subjects, among the subjects within the scope of Islamic education in madrasah is, the Qur'an and the Hadits, Aqidah, Fiqh, Akhlaq and history of Islamic culture. In our society today, the subjects of Islamic Education in public school and subjects Aqidah Akhlaq if at the madrasa has seized the attention of serious. One side of this community's attention is positive due to the level of concern they would be the development of morals to their children. However, on the other hand is negative because the pie or Aqidah Morals they consider failed in controlling its morals (character) so that their children have a premature character alias character is bad. The reality of religious teachers who are just concerned with mere religious knowledge transfer lead to absorption of learners will meaning and religious values has not carried. Respond to such anxieties, need a new breakthrough and formula or to compromise the gap that occurs between the religious competence with the practice in the everyday life of learners. So the presence of Islamic religious education based on the values of the character who spearheaded the University Laboratory elementary school Stanford felt the need to be reviewed and applied.